Developing an Inclusive School Model to Enhance Educational Service Quality for Students with Special Needs in Bukittinggi City - Ezi Mulia; Silfia Hanani (International Journal of Advanced Studies in Educational Management (IJASEM), 2026)
Inclusive education has been formally mandated in Indonesia; however, its implementation at the school level remains inconsistent, particularly in managing students with special needs. This study aims to analyze school management practices in implementing inclusive education in two primary schools in Bukittinggi City. A qualitative case study design was employed, involving principals and teachers from SDIT Al-Azhar Darul Jannah and SD Negeri 04 Birugo as key informants. Data were collected through observations, semi-structured interviews, and document analysis, and analyzed using thematic analysis with source triangulation to ensure validity. The findings reveal that both schools implement inclusive education through five key management dimensions: student identification and assessment, educator adaptation, curriculum modification using Individualized Learning Programs and Universal Design for Learning, flexible evaluation systems, and partial adjustment of infrastructure. Despite these efforts, major constraints include limited specialized human resources, inadequate facilities, and low parental involvement. This study contributes to the literature by demonstrating how adaptive school management strategies can sustain inclusive practices in resource-constrained settings, highlighting the importance of collaborative governance and capacity building for improving inclusive education outcomes.